Effects of Gallic Acid on Fermentation Parameters, Protein Fraction, and Bacterial Community of Whole Plant Soybean Silage - Wang, Cheng; Zheng, Mingyang; Wu, Shuo; Zou, Xuan; Chen, Xiaoyang; Ge, Liangfa; Zhang, Qing (Frontiers in Microbiology, 2021)
Whole plant soybean (WPS) is a kind of legume resource with characteristics of high nutrition, large biomass and wide distribution. And in order to investigate the feasibility and effects of GA on WPS silage quality, nitrogen distribution, tannin content and bacterial community. The 0.5% and 1% (fresh matter basis) GA were added into WPS for dynamically ensiling (day 3, 7, 14 and 30, respectively). The results showed that the WPS silage with GA addition significantly decreased pH value (6.16 to 5.38 at ensiling day 30), coliform bacteria count and BA (65.3 to 62.0 g/kg dry matter at ensiling day 30), NH3-N contents (259 to 88.2 g/kg total nitrogen at ensiling day 30), and promoted LA (9.62 to 31.5 g/kg dry matter at ensiling day 30), AA (24.1 to 85.6 g/kg dry matter at ensiling day 30), and tannin (total phenol and hydrolysable tannin) contents. Additionally, the GA addition also contribute to the change of bacterial community, where Firmicutes and Lactobacillus were most abundant on phylum and genus level, respectively. The above results suggested that GA additive applied in WPS silage was an effective strategy to protect nutrition and improve fermentation quality, and the 1% GA addition showed a better effect.